New Languages and Technologies for Delivering Learning and Multimedia Contents – XAML and WPF - Mateljan, Vladimir (Array, 2008)
Modern learning contents, besides traditional media for delivering contents – text, also contain multimedia elements, first of all audio and video. In order to include multimedia elements in learning systems, it was necessary to wait for significant increase in the bandwidth of local and access networks that has occurred in recent couple of years. Since multimedia contents has much bigger requirements on network and computer environments than simple text content does, the acceptance of multimedia in learning contents was conditioned mostly with available bandwidth. Today, most systems designed for delivering learning contents are built as client-server applications. In those applications, server takes care of delivering learning contents to client applications, and client applications take care of presenting that content to their users. Since every user wanting to use learning system must have a copy of client application on his or her computer, it is very important for those client applications to be simple and easy redistributable. In most cases, an Internet browser is being used as a client application. The main reason for that is the fact that there is at least one Internet browser on every computer, regardless of its operating system, so there is no need for installing additional application packages. That allows users to start using learning contents immediately, allows easier maintenance of client application, and allows the use of learning contents from any available computer. Historically, Internet browsers were designed for displaying text and images only. The advance of multimedia put the challenge of handling those new media in Internet browsers, but they did not cope with that task very well. The need for distributing multimedia elements to users through Internet browsers led to using add-ins to browsers that were designed specifically for handling multimedia contents. The most popular browser add-ins for delivering learning contents are Adobe Flash Player and Macromedia Authorware (as its vendor claims, 98% of Internet users have Adobe Flash Player installed in their browsers. In year 2007, the new technology was designed and produced for delivering multimedia contents through Internet browsers. That new technology was named Silverlight